Pengaruh Sosialisasi, Pengetahuan, Sanksi Perpajakan, dan Tax Amnesty Terhadap Kepatuhan Wajib Pajak Orang Pribadi : Studi Kasus Pada KPP Bekasi Utara - Riska Dwi Nurcahyani; Cris Kuntadi; Rachmat Pramukty (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
The purpose of this research is to examine and analyze the Influence of Socialization, Knowledge, Tax Sanctions, and Tax Amnesty on the Compliance of Individual Taxpayers. This research method uses a quantitative research method, with the type and source of data being primary data obtained from the distribution of questionnaires. The population and sample of this study are taxpayers registered at KPP Pratama Bekasi Utara. The sampling technique used is purposive sampling with nonprobability sampling involving 112 respondents. The analysis methods used are descriptive statistical tests, validity tests, reliability tests, normality tests, multicollinearity tests, heteroscedasticity tests, t-tests (partial), F-tests (simultaneous), coefficient of determination (r2) tests, and multiple linear regression tests. The results of this study indicate that tax socialization has a positive and significant effect on the compliance of individual taxpayers at KPP Pratama Bekasi Utara, tax knowledge does not affect the compliance of individual taxpayers at KPP Pratama Bekasi Utara, tax sanctions have a positive and significant effect on the compliance of individual taxpayers at KPP Pratama Bekasi Utara, tax amnesty does not affect the compliance of individual taxpayers at KPP Pratama Bekasi Utara, and tax socialization, tax knowledge, tax sanctions, and tax amnesty simultaneously (together) have a positive and significant effect on the compliance of individual taxpayers.